MULTICULTURALISM IN CONTEXT: ISLAM, INDONESIAN, ANDGLOBAL CHALLENGE - Arief Subhan (TASÂMUH, 2017)
Various cultures, races, ethnics, and religions grow and flourish in Indonesia. However, conflict events due to cultural differences, ethnicities, ethnicities, and religions indicate that communication, mutual understanding, and recognition of others (which in the language of social science is called multiculturalism or “pluralistic culture” This reform and openness is even more important and urgent to be included in the agenda of every religion, especially the da’wah agenda. In today’s diverse society there is a need for a new world setting where cultural differences, belief systems, and values do not trigger social divisions and conflicts. Instead, serve as a backdrop to encourage the excitement of human beings to get to know each other. In managing diversity as a social reality as in Indonesia, which is needed not only recognition and acceptance; Not just tolerance for diversity and diversity; More than all it is a willingness to cooperate and cultivate unity as a nation. In addition, every ethnic, cultural, and religious group in Indonesia should also have a view of the same “imagined communities”